Hesse Pencils and 3-Torsion Structures - Anema, A.S.I.; Top, J.; Tuijp, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
This paper intends to focus on the universal property of this Hesse pencil and of its twists. The main goal is to do this as explicitly and as elementary as possible, and moreover to do it in such a way that it works in every characteristic different from three.